Carbon Footprint In Surat City Household - et. al., Deeksha Sehgal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The carbon footprint has a great impact on our environment which is caused by our day to day activities. A Google form was made to collect the data related to carbon footprint which involves various parameters like electricity consumption, LPG consumption, cylinder consumption; petrol etc. And from the results obtained by the survey in the seven zones in Surat have different values of consumption and different values of emission of CO2 which were calculated with the help of a carbon footprint calculator (approved by ISO). Total Carbon Footprint: 261.1 Ton Of CO2 and Average: 5.2 Tonnes of CO2. According to the zone wise calculated data it is observed that the zones which have higher value of CO2 emission have the medium or large size of home, their lifestyle like use of electrical appliances, the type of food they prefer, waste and plastic produced, purchases they do, transportation modes they use etc. have a great impact on the carbon footprint.